2016
DOI: 10.1103/physreve.94.032221
|View full text |Cite
|
Sign up to set email alerts
|

Estimability and dependency analysis of model parameters based on delay coordinates

Abstract: In data-driven system identification, values of parameters and not observed variables of a given model of a dynamical system are estimated from measured time series. We address the question of estimability and redundancy of parameters and variables, that is, whether unique results can be expected for the estimates or whether, for example, different combinations of parameter values would provide the same measured output. This question is answered by analyzing the null space of the linearized delay coordinates m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…EEG data, as well as data obtained from several other methods, is thus used to shed light into the binding connecting network structures678910 and the strengths of the neuron synapses in the brain. Modelling EEG signals is essential to understand the anatomy and histophysiology of the brain, and therefore provide support to medical imaging analysis and to the development of neuroscience11. However, consensus about what is the topology of the brain or its synaptic modus operandi is still an open problem.…”
mentioning
confidence: 99%
“…EEG data, as well as data obtained from several other methods, is thus used to shed light into the binding connecting network structures678910 and the strengths of the neuron synapses in the brain. Modelling EEG signals is essential to understand the anatomy and histophysiology of the brain, and therefore provide support to medical imaging analysis and to the development of neuroscience11. However, consensus about what is the topology of the brain or its synaptic modus operandi is still an open problem.…”
mentioning
confidence: 99%
“…However, a weak linear correlation does not mean that there is no coupling relation between the variables. Previous studies (Sugihara et al, 2012;Emile-Geay and Tingley, 2016) have suggested that although the linear correlation of two variables is potentially absent, it might be nonlinearly coupled. For instance, the linear cross-correlations of sea air temperature series observed in different tropical areas are overall weak, but they can be strong locally and vary with time (Ludescher et al, 2014); such a time-varying correlation is an indicator of nonlinear correlation (Sugihara et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies (Sugihara et al, 2012;Emile-Geay and Tingley, 2016) have suggested that although the linear correlation of two variables is potentially absent, it might be nonlinearly coupled. For instance, the linear cross-correlations of sea air temperature series observed in different tropical areas are overall weak, but they can be strong locally and vary with time (Ludescher et al, 2014); such a time-varying correlation is an indicator of nonlinear correlation (Sugihara et al, 2012). These nonlinear correlations of the sea air temperature series have been found to be conductive to the better El Niño predictions (Ludescher et al, 2014;Conti et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations